2013
DOI: 10.1038/ki.2012.421
|View full text |Cite
|
Sign up to set email alerts
|

The adipose tissue production of adiponectin is increased in end-stage renal disease

Abstract: Adiponectin has anti-diabetic properties and patients with obesity, diabetes and insulin resistance have low plasma adiponectin levels. However, although kidney disease is associated with insulin resistance, adiponectin is elevated in end stage renal disease. Here we determine if adipose tissue production of adiponectin is increased in renal disease in a case-control study of 36 patients with end stage renal disease and 23 kidney donors. Blood and tissue samples were obtained at kidney transplantation and dona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 35 publications
(43 reference statements)
2
50
2
1
Order By: Relevance
“…The upregulation of the adiponectin production rate as a compensatory mechanism to mitigate further renal injury appears to be the main cause of increased serum adiponectin levels in patients with advanced albuminuria. As mentioned above, the elevation of adiponectin expression and production in the setting of human renal disease has been demonstrated only in patients with end-stage renal disease (Martinez Cantarin et al 2013). Although, Komura et al (2010) reported that adiponectin production in the adipose tissue of subtotal nephrectomised mice did not change at 1 month after operation, the time duration of 1 month may be too short to elicit a full-blown upregulation of adiponectin production.…”
Section: Serum Adiponectin Levels In Patients With Albuminuriamentioning
confidence: 97%
See 1 more Smart Citation
“…The upregulation of the adiponectin production rate as a compensatory mechanism to mitigate further renal injury appears to be the main cause of increased serum adiponectin levels in patients with advanced albuminuria. As mentioned above, the elevation of adiponectin expression and production in the setting of human renal disease has been demonstrated only in patients with end-stage renal disease (Martinez Cantarin et al 2013). Although, Komura et al (2010) reported that adiponectin production in the adipose tissue of subtotal nephrectomised mice did not change at 1 month after operation, the time duration of 1 month may be too short to elicit a full-blown upregulation of adiponectin production.…”
Section: Serum Adiponectin Levels In Patients With Albuminuriamentioning
confidence: 97%
“…Thus, in patients with increased UAE or decreased GFR, the adiponectin production rate -hepatic adiponectin excretion rateappears to be increased. This elevation could be attributed to an increased rate of adiponectin production, because adiponectin expression and adiponectin protein content in visceral as well as subcutaneous adipose tissue were found to be increased in patients with end-stage renal disease (Martinez Cantarin et al 2013). Studies investigating the possible modulation of hepatic adiponectin excretion rate in patients with renal disease are lacking, and thus further studies investigating this issue are needed.…”
Section: Urinary Adiponectin Excretion Rate In Patients With Albuminuriamentioning
confidence: 99%
“…51 According to Cantarin and coworkers, increased plasma adiponectin levels observed in ESRD are accompanied by an increase in adiponectin protein and mRNA expression in human subcutaneous and visceral adipose tissues, suggesting that there is a stimulus to produce more adiponectin protein despite elevated plasma levels. 52 A recent study demonstrated that there is higher expression of AdipoR1 in muscle tissue of ESRD patients compared to controls with normal kidney function. 53 Increased adiponectin production and increased AdipoR1 receptor expression, despite increased adiponectin levels, indicate that uremia confers adiponectin resistance.…”
Section: Circulating Adiponectin Levels In Esrd Patientsmentioning
confidence: 99%
“…67,68 In visceral fat and muscle of ESRD patients, AdipoR1 mRNA expression is increased, whereas expression of AdipoR2 is not modified by uremia. 52 Thus, adiponectin resistance with high levels of adiponectin but relatively low AdipoR2 may contribute to an impairment of adiponectin-stimulated fatty acid oxidation and lead to insulin resistance.…”
Section: Adiponectin and Insulin Resistance In Esrdmentioning
confidence: 99%
See 1 more Smart Citation